Pemberdayaan Potensi Masyarakat Melalui Pengembangan Perdagangan, Pendidikan, Sosial, dan Lingkungan Desa Gedangan Kecamatan Grogol Kabupaten Sukoharjo - Puspanda Hatta; Agus Budiarto; Imam Prasetyo; Putri Karimah; Abdillah Yusron (DEDIKASI: Community Service Reports, 2021)
Gedangan is a village located in Grogol District, Sukoharjo Regency, Central Java. In 2021, Gedangan Village will become one of the partners of the Sebelas Maret University Student Community Services Program (KKN). In this village, KKN activities were carried out using a hybrid system due to the pandemic. KKN is carried out through online and offline activities with the theme of empowering community potential through counselling in the fields of animal husbandry, education, social and creative industries. The work programs that have been implemented are "Literacy Lanterns", Catfish Cultivation in Buckets, composter making, educational posters, PHBS counselling, Reading Houses, and murals to attract the public. The implementation strategy includes socialization, teaching, and various trainings. With this KKN team work program, the people of Gedangan Village are able to optimize the local potential of the village, especially in the fields of Education, Social, and Creative Industries. This activity is supported by the village government and local communities from various backgrounds. This activity is useful for developing Gedangan Village in managing village potential and can help the community be more interested in developing Gedangan in the future.